Cascade of care for HIV-seroconverters in rural Tanzania: a longitudinal study. Issue 5 (3rd May 2020) - Colombe, Soledad; Machemba, Richard; Mtenga, Baltazar; Lutonja, Peter; Safari, Wende; Beard, James; Downs, Jennifer A.; Urassa, Mark; Todd, Jim; Changalucha, John
ABSTRACT: We examined the HIV care cascade in a community-based cohort study in Kisesa, Magu, Tanzania. We analyzed the proportion achieving each stage of the cascade – Seroconversion, Awareness of HIV status, Enrollment in Care and Antiretroviral therapy (ART) initiation – and estimated the median and interquartile range for the time for progression to the next stage. Modified Poisson regression was used to estimate prevalence risk ratios for enrollment in care and initiation of ART. From 2006 to 2017, 175 HIV-seroconverters were identified. 140 (80%) knew their HIV status, of whom 97 (69.3%) were enrolled in HIV care, and 87 (49.7%) had initiated ART. Time from seroconversion to awareness of HIV status was 731.3 [475.5–1345.8] days. Time from awareness to enrollment was 7 [0–64] days, and from enrollment to ART initiation was 19 [3–248] days. There were no demographic differences in enrollment in care or ART initiation. Efforts have been focusing on shortening time from seroconversion to diagnosis, mostly by increasing the number of testing clinics available. We recommend increased systematic testing to reduce time from seroconversion to awareness of status, and by doing so speed up enrollment into care. Interventions that increase enrollment are likely to have the most impact in achieving UNAIDS targets.